The role of B cells in the pathogenesis of type 1 diabetes - Wang, Ya-nan; Li, Ruihua; Huang, Yaxuan; Chen, Hui; Nie, Hao; Liu, Lian; Zou, Xiaoting; Zhong, Jixin; Zheng, Bing; Gong, Quan (Frontiers in Immunology, 2024)
Type 1 diabetes (T1D) is a metabolic disorder caused by a complete lack of insulin, primarily manifested by hyperglycemia. The mechanisms underlying the onset of T1D are complex, involving genetics, environment, and various unknown factors, leading to the infiltration of various immune components into the islets. Besides T cells, B cells are now considered important contributors to the pathogenesis of T1D, according to recent studies. In non-obese diabetic (NOD) mice, the absence of B cells prevents the development of T1D, and B-cell depletion can even restore the function of pancreatic β cells, emphasizing their involvement in the development of T1D. Naturally, besides pathogenic B cells, regulatory B cells (Bregs) might have a protective function in T1D. This article examines the mechanisms behind B-cell tolerance and the defects in B-cell tolerance checkpoints in T1D. We explored possible functions of B cells in T1D, including the role of islet autoantibodies in T1D, T–B cell interactions, and the role of Bregs in the pathogenesis of T1D. We also summarized the advances of B cell-targeted therapy, exploring new methods for intervention and treatment of T1D.